PENDAMPINGAN DAN PENYALURAN BANTUAN 5 JUTA BENIH UDANG DAN 10 RIBU BENIH IKAN KAKAP PUTIH BAGI PEMBUDIDAYA IKAN DI KECAMATAN UJUNGPANGKAH, KABUPATEN GRESIK - Aminin Aminin; Suhaili Suhaili; Andi Rahmad Rahim; Muh. Sulaiman Dadiono (PT. Gyandharma Global Media, 2025)
This community service activity aims to increase the productivity of fish farmers through a shrimp and white snapper seed assistance program organized by the Indonesian Ministry of Maritime Affairs and Fisheries (KKP). The activity was carried out on March 1, 2018, in Ujungpangkah District, Gresik Regency, East Java, with 150 participants from fish farmer groups. The implementation method included data collection of recipient groups, distribution of seed assistance, and brief technical assistance related to seed maintenance. The results of the activity showed that farmers gained direct access to quality seeds, which is expected to increase cultivation productivity. Obstacles encountered included the absence of several farmer groups and protests regarding the distribution of assistance. Overall, this activity had a positive impact on the sustainability of fish farming businesses in Ujungpangkah District.